PERUBAHAN PERILAKU MALADAPTIF DENGAN JADWAL TERSTRUKTUR PADA ANAK AUTISME - Siti Nuraini Purnamawati, Suprihatin, (Perspektif Ilmu Pendidikan, 2013)
This research aimed at discovering the maladaptive bevavior change of the subject that is turning his/her head towards the window, leaving the seat to search the bee during the lesson after the child had been given the treatment using a structured schedule which fit to the peculiar characteristics of his/her maladaptive behavior objective. The research was conducted at SLB Tegar Harapan in Sleman (IY) as from June through Novemebr 2012. The research subject was an autistic child continuaously showing maladaptive behavior as mentioned before that made him not concentrate to rthe lesson. As a Single Subject Research with ABA design, this research applied obervation method to collect the data to be analyzed with simple technique. The findings showed in general the frequency of maladaptive behavior showed by the subject tent to decrease up to 1. Based on the findings, the research suggested to implement this method for other autistic children /more population to prove the effectiveness of the method.